Tryptophan hydroxylase 2 gene is associated with cognition in late-onset depression in a Chinese Han population - Wang, Xiaoquan; Wang, Zusen; Wu, Yanfeng; Hou, Zhenghua; Yuan, Yonggui; Hou, Gang (Neuroscience letters, 2015)
•There may be a major effect in TPH2 gene on cognition in LOD patients alone.•An interaction of TPH2 gene and depression may be affect the cognition in LOD.•Some domain of cognition may be affected by the severity of depression. Accumulating evidences suggest that Tryptophan hydroxylase 2 (TPH2) gene is associated with major depressive disorder (MDD) and cognitive function. In present study, we aimed to explore the association of cognitive disturbances in patients with late-onset depression (LOD) in the Chinese Han population. One hundred and ninety unrelated LOD patients who met DSM-IV criteria for major depressive disorder were recruited for the study and 155 normal controls were recruited from local community. All subjects completed the demographic assessments. Furthermore, 97 patients and 44 controls completed a series of neuropsychological tests. Patients and normal controls were genotyped for TPH2 (rs4290270 and rs7305115) variants using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The results of our analysis indicated no significant differences in the frequencies of the single alleles and genotypes of two polymorphisms in TPH2 gene between LOD patients and normal controls. Haplotype association indicated that no differences were found in the frequencies of haplotype between two groups. A significant main effect of rs4290270 genotype on Verbal Fluency Test (VFT) test performance was found (P<0.05). There was a significant interactive effect of rs7305115 polymorphisms and depression diagnosis on Symbol Digit Modalities Test (SDMT) (P<0.05). After controlling for covariates, the subjects with carriers of GG genotype in rs7305115 had more better SDMT performance compared to AG and AA carriers in LOD groups. The result suggests that there is a major effect of rs4290270 in TPH2 on cognitive function alone. Moreover, an interaction of rs7305115 polymorphisms and depression diagnosis may be associated with the cognitive function. Further studies in a large sample are needed to replicate the genetic role in the LOD patients.